2011
DOI: 10.1103/physrevb.83.155321
|View full text |Cite
|
Sign up to set email alerts
|

Experimental quantitative study into the effects of electromigration field moderation on step bunching instability development on Si(111)

Abstract: We experimentally studied the effects of a moderated electromigration field on the dynamics of the step bunching process on the Si(111) surface at 1130 • C (regime II) and 1270 • C (regime III). The surfaces with step bunch morphologies were created by annealing vicinal Si(111) at fixed temperatures while the applied electric field E was adjusted for every experiment. Scaling relations, y m ∼ h α E q , between the slope of a step bunch y m , step bunch height h, and electromigration field E were experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…These step bunches grow with time and reach tens to hundreds of nanometers in height, while the terraces between them can grow to several micrometers in width. 1,2,10 Soon after the discovery of step bunching, it was found that prolonged dc annealing of Si(111) allows the surface morphology to further develop, giving rise to new morphologies such as antibands, which can be described as step bunches with slopes of the opposite sign as compared to the primary bunches. 11 Antibands are primarily formed via the shape evolution of atomic steps crossing the wide terraces between step bunches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These step bunches grow with time and reach tens to hundreds of nanometers in height, while the terraces between them can grow to several micrometers in width. 1,2,10 Soon after the discovery of step bunching, it was found that prolonged dc annealing of Si(111) allows the surface morphology to further develop, giving rise to new morphologies such as antibands, which can be described as step bunches with slopes of the opposite sign as compared to the primary bunches. 11 Antibands are primarily formed via the shape evolution of atomic steps crossing the wide terraces between step bunches.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] When Si(111) is annealed by direct current (dc) driven along the miscut direction, adatom surface electromigration causes the atomic steps to gather together and creates step bunches separated by wide terraces. These step bunches grow with time and reach tens to hundreds of nanometers in height, while the terraces between them can grow to several micrometers in width.…”
Section: Introductionmentioning
confidence: 99%
“…The step bunching due to heating by direct current has been well documented on the Si(111) surface with 1° miscut angle1516. It was observed that the step bunching was influenced by either annealing temperature or the direction of current flow.…”
Section: Resultsmentioning
confidence: 89%
“…The phenomenon that the variation of terrace width of Si(111) substrate with heating current direction can be explained by the surface electromigration of Si adatoms1516. The step bunching due to heating by direct current has been well documented on the Si(111) surface with 1° miscut angle1516.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation